From gaming to reality: effectiveness of skills transfer from competitive sandbox gaming environment to near and far contexts - Yuchun Zhong; Luke Kutszik Fryer; Shiyue Zheng; Alex Shum; Samuel Kai Wah Chu (International Journal of Educational Technology in Higher Education)
Abstract Esports or competitive video gaming has been increasingly utilized to enhance essential twenty-first century skills. However, there is limited evidence on the extent to which the skills acquired from a gaming environment can be transferred to other settings. This study employed an experimental design to investigate the effectiveness of a competitive sandbox game environment in enabling the transfer of the 4Cs skills to both near and far tasks, in contrast with a non-game environment. A cohort of 110 students from a university were randomly allocated to both conditions for the 4Cs skills training. The skills transferability was measured through self-reports, observations, and interviews. The findings indicated no significant differences in the transfer of creativity, critical thinking, and communication skills in near and far settings following both training environments. Interestingly, a competitive gaming environment significantly facilitated the transfer of collaboration skills to near tasks evidenced by performance-based assessments. Moreover, although the hypotheses 1c and 3c were not statistically supported, the small to medium effect size suggests that there were practical differences between the groups in self-reported collaboration skills in near and far tasks. Additionally, analysis of individual interviews with 41 participants indicated that the successful transference was attributed to an array of scaffolds (i.e., mentorship, collaborative problem-solving environment, autonomy, and guided checklists) while the failure to detect positive effects was explained by various constraints (i.e., unfamiliarity with game rules, limited time, lack of practice, and established cognitive patterns). These findings add new insights into the literature on game-based learning and transfer of learning and inform researchers to further investigate the longitudinal effect of skills transfer and retention in both academic and professional spheres.